Captive funds and banks' capital - Arayssi, Mahmoud (2018)
A simple leverage ratio restriction is not efficient because it does not discriminate between risky and safe banks.We use a structural and comprehensive model of the firm’s asset growth to describe the equity buyout portfolios’ stylized facts for two types of banks.We derive a leverage ratio that depends on the level of risky investments, and balances between the spread on such investments, the cost of capital and the overall power of the supervisor to enforce the capital requirements. This method is more transparent and requires fewer parameters than other commonly used methods. We obtain an incentive-compatible constraint on banks to carry the minimal adequate amount of capital. This constraint enhances the supervisors’ ability to enforce the rules ex post, and provide banks with a further incentive to reveal their risk type truthfully.